A Interactive Game to Enhance Student Understanding of Materials Management - William E. Mueller; Gholam H. Massiha (International Journal of Evaluation and Research in Education (IJERE), 2012)
It is difficult for students to grasp essential concepts of materials management because there is a considerable amount of new terminology as well as the need to develop a “feel” for what appears to be a static, but in actuality, a very dynamic process. In an attempt to overcome the language barrier as well as help the student develop a “feel” for the process, an old case study from the 70s has been revised and updated it for today’s student.  The method of presentation has also been changed from an out-of class activity to an in-class group activity. Initial results, based on 3 classes of 35-40 students each, have been positive with absenteeism reduced from a historical average of 10-15% down to 2%.  Student attitude appears to be better and test results appear to be better although comparisons in this area are more difficult to measure. A copy of the game is provided and maybe be freely used in your classroom.   Any suggestions for improvement would be greatly appreciated.DOI: http://dx.doi.org/10.11591/ijere.v1i2.1485